The Fishermen and the Deep: Diving and Distant-water Fisheries, the Case of the Light Divers of the State-owned Fisheries of the German Democratic Republic (GDR) - Heidbrink, Ingo (Journal for the History of Environment and Society, 2024)
Abstract This article aims to provide an overview of the developments that resulted in the use of light divers onboard GDR distant-water fishing vessels as well as the technological, organizational, and administrative challenges of implementing the idea. It also discusses why this concept remained unique to the GDR fishing fleet. Prior to looking at the specific development in the GDR, the article will provide an overview of the relation of distant-water fishermen with the world underwater and why it remained for fishermen onboard GDR fishing vessels a black-box, while fishermen from western fishing nations could gain limited indirect access to the world underwater with the help of highly sophisticated technology. In a broader analytical perspective, the issue will be raised if the use of light divers should be understood as an element of the GDR culture of improvisation, explaining why other distant-water fishing nations did not opt for the concept of using light or scuba divers to support their distant water fishing fleets.
Keywords: Fischkombinat